Corporalidade despedida: da exterioridade marxiana à opção pela vítima em Enrique Dussel - Sezyshta, Arivaldo José (2014)
The objective of this study is no present the Critical Politic Philosophic of Liberation from Enrique Dussel, analyzing its genesis and evolution and showing the decisive influence of praxis philosophy of Karl Marx for this thinking, especially since the concept of externality, understood as the context where the other reveals himself, where he remains free on your distinct being. The exteriority precisely, is regarded here as the main category of Marx's legacy and fundamental theoretical assumption, which enables the speech Dussel, especially in radical option for the victim, his philosophical thinking brand. Through this, here assumes the thesis that there is a partiality in Dussel by the victim: your thinking is built purposely in favor of the victim. The effort of this work is to show that the choice of the victim shall be the guiding principle for all their thinking as Philosophy of Liberation, through the Ethics and the Politics, coming to the bringing of an Economic Liberation. For this, as a strategic approach, the externality and liberation categories delineate the philosophical analysis to the necessary approach to their theme, by reading the major works of Dussel, in dialogue with the philosophy of praxis Marx. As an extension of the hypothesis proposed, it intends to show how the choice of victim charges the Philosophy of Liberation critical pretense of thought, from three perspectives: through an Ethics of Liberation, as a critical pretense of kindness, from a Politics of Liberation, guided by a political pretense of justice, and an Economy of Liberation, requiring an economic pretense of fairness. Thus, the philosophical work is challenged and provoked by the real need to assist the victim, a requirement of the Latin American people in their path of liberation. In terms of results, beyond the current importance of Marx's thought for the comprehension of reality and the critique of capitalism, emphasizes the relevance of the theoretical and practical of Dussel‟s thoughts to Political Philosophy as a whole, for their contributions in the contemporary scenario, the courage to point toward another society, trans-modern and trans-capitalist, already in progress in collective practices of Living Well.